Pembuatan konten video usaha gula aren sebagai sarana promosi masyarakat Desa Batu Mila, Maiwa, Enrekang - Al Munawar; Angsal Suardi; M. Nur Ikshsan; Fahrul; Chadija Karim; Wildayanti; Wiwi Pratiwi A; Mulya Magfirah; Nurfitriani Fatimah; Nurlinda; Hidayah Saleh; Suherman (P3HKI - Universitas Muhammadiyah Parepare, 2020)
Aren Sugar is one of the sweeteners that have been produced by the Indonesian people for a long time. Sugar is an alternative food ingredient and is a side livelihood for some people and has become a micro-enterprise in Batu Mila Village. The purpose of making Aren Sugar business video content is as promotional media because Aren Sugar marketing in Batu Mila Village does not yet have such a wide reach. The Aren Sugar business video content will then be uploaded via YouTube so that with the Aren Sugar production video content it can be better known by the wider community and Aren Sugar marketing will continue to grow. It is suggested the a need for the formation of farmer groups with the aim of uniformity in the market price of Aren Sugar. So that Aren Sugar products can be sold in the modern market.